A New Phase of Women in Rama Mehta’s: Inside the Haveli and The Western Educated Hindu Women - et.al, Afsana Bano (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This particular work reveals the voyage of Geeta in the cross-cultural context and also the perception of society towards a daughter-in-law with reference to both the works of Rama Mehta. The concepts like child marriage and education are focused here, while influencing the life of the protagonist directly or indirectly. She expresses the psychological and emotional struggle of a woman’s search for self identity. In this work I have tried to introduce a new phase of feminism with the works of Rama Mehta and proved that modern women are not dominated and subordinated by any force of society, as she possess the power to take her own decision and can stand on their own capabilities. Now the women are empowered and independent